Sex‐specific associations of human milk long‐chain polyunsaturated fatty acids and infant allergic conditions. Issue 6 (31st March 2021) - Miliku, Kozeta; Richelle, Jacqueline; Becker, Allan B.; Simons, Elinor; Moraes, Theo J.; Stuart, Turvey E.; Mandhane, Piush J.; Sears, Malcolm R.; Subbarao, Padmaja; Field, Catherine J.; Azad, Meghan B.
Abstract: Background: Polyunsaturated fatty acids (PUFAs) may influence immune development. We examined the association of PUFAs in human milk with food sensitization and atopic dermatitis among breastfed infants. Methods: In a selected subgroup of 1109 mother‐infant dyads from the CHILD Cohort Study, human milk was analyzed by gas‐liquid chromatography to quantify PUFAs including arachidonic acid (ARA) and docosahexaenoic acid (DHA). At 1 year of age, food sensitization was determined by skin‐prick testing for egg, peanut, cow's milk, and soybean, and atopic dermatitis was diagnosed by pediatricians. Logistic regression analyses controlled for breastfeeding exclusivity, family history of atopy, and other potential confounders. Results: Overall, 184 infants (17%) were sensitized to one or more food allergens and 160 (14%) had atopic dermatitis. Sex‐specific associations were observed between these conditions and milk PUFAs. Girls receiving human milk with lower proportions of DHA had lower odds of food sensitization (aOR 0.35; 95% CI 0.12, 0.99 for lowest vs highest quintile), and a clear dose‐dependent association was observed for the ARA/DHA ratio (aOR 2.98; 95% CI 1.10, 8.06 for lowest vs highest quintile). These associations were not seen in boys. Similar sex‐specific tendencies were observed for atopic dermatitis. Conclusions: Human milk PUFA proportions and their ratios are associated with infant atopic conditions in a sex‐specific manner. In female infants, a higher ratio of ARA/DHA may reduce the risk of food sensitization and atopic dermatitis. Further research is needed to determine the underlying mechanisms and clinical relevance of this sex‐specific association.